Asymmetric dimethylarginine is not a good predictor of ischemia using myocardial perfusion scintigraphy - (:unkn) unknown (My University, 2015)
0

Background/aim: Asymmetric dimethylarginine (ADMA) plays role in the pathogenesis of coronary artery disease and related mortality and morbidity through a number of mechanisms. We hypothesized that plasma ADMA levels would be increased in the presence of reversible ischemia as measured by GATED single photon emission computed tomography (SPECT) myocardial perfusion scintigraphy (MPS). Materials and methods: Fasting i.v. blood samples were drawn before testing. All patients underwent 99mTc-sestamibi GATED SPECT MPS with a one-day stress-rest protocol; the images were visually analyzed. Post-stress GATED parameters, including ejection fraction, end systolic and end diastolic volumes, and automatic stress defect scores, were recorded. Results: The plasma ADMA levels were higher in the ischemic group than in the non-ischemic group (0.46 ± 0.19 vs. 0.40 ± 0.15; P = 0.016). Plasma ADMA levels (odds ratio [OR] = 13.5; 95% confidence interval [CI] = 1.7-109.01; P = 0.015) and sex (OR = 2.49, 95% CI = 1.18-5.26; P = 0.017) were independent predictors of ischemia. There was no linear correlation between plasma ADMA levels and both the GATED SPECT and stress test parameters. Conclusion: Our data support the hypothesis that increased baseline ADMA levels are independently related with the presence of reversible ischemia.
Keywords: Cerrahi